The new European phenomenon, health tourism : present situation - Isabel Casabona Martínez; Manuel Lillo Crespo; María Dolores Mora Antón; Roberto Galao Malo (Universidad de Alicante, 2012)
The present crisis in health system is something common world wide. This crisis can be well detected when watching waiting lists for surgical care treatments, according to the increasing number of operation processes due to the better present surgical and anesthetic techniques. Also due to the more and more demands from the population. This is a process where finance for certain specific processes emphasizes. The health systems are looking for alternative ways to diminish their waiting lists as well as to decrease costs. For that reason, the European Union opens its borders to easy a possible traffic of patients among different countries to allow users of a certain Union Estate to move to another one. In some occasions a full team of professionals: doctors and nurses could move from their own European Estate to a different one. But of course, this type of transfers do present certain problems. The native country must guarantee that the care the patient will get in another country will be similar to its own. The receiving country faces the challenge of caring patients with a different culture, a different language and as a consequence different ways for considering health where illness and hospitalization differ as well. Clinica Vistahermosa - in Alicante - has been pioneer in that sense, in the whole Spain, and within Europe. CV. has agreements and protocols signed with Portugal, U.K. and Holland. As a matter of fact, it has been receiving patients from the later for several years now. As we have been showing in several studies, there is a new phenomenon we may call "Health Tourism" in Alicante, as patients integrate not only for health techniques but for leisure time as well as they book hotel rooms for post-operative sessions. Present situation, challenges and consequences of this new phenomenon are presented in this study.